Pathological aspects of life at high altitudes - Hurtado, Alberto (1956)
Man in high altitudes lives in constant anoxic. Due to the partial reduction of the oxygen pressure in the inspired air, hemoglobin is normally not saturated during the circulation of blood through the lungs and then occurs, simultaneously, a decrease in the tension of the small fraction of this gas physically dissolved in the plasma. In these circumstances an adequate supply of oxygen to the tissues is difficult. Most of the investigations in this field have been directed to the study of disorders that are generally presented at the beginning of exposure to altitude and knowledge of adaptive mechanisms that occur in the majority of cases, leading to a adaptive to process low oxygen pressure. Comparatively less attention has been given to man born and raised in this environment and its location between healthy subjects has been discussed yet.